2018
DOI: 10.1002/apj.2264
|View full text |Cite
|
Sign up to set email alerts
|

Experimental measurements and modelling of CO2 solubility in aqueous mixtures of benzylamine and N‐(2‐aminoethyl) ethanolamine

Abstract: In this work, carbon dioxide solubility in N-(2-aminoethyl) ethanolamine (AEEA) activated aqueous benzylamine (BZA) solutions are studied using a stirred-cell reactor in the temperature and pressure range of 313.15-333.15 K and 0.2-219 kPa, respectively. AEEA is a linear diamine with a primary and secondary amine groups, and BZA is a primary cyclic amine. The concentration of the aqueous blends used are (20mass% BZA + 10mass% AEEA), (24mass% BZA + 6mass% AEEA), and (28mass% BZA + 2mass% AEEA).Density and visco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Kim and Svendsen have reported the experimental data on the heat of absorption of CO 2 in 30 wt % AEEA solution in a reaction calorimeter, which is the only available information in the literature on the direct calorimetric measurements of the enthalpy of absorption of CO 2 for the system (CO 2 + AEEA + H 2 O). The results on CO 2 solubility and physical properties in our previous study concluded the use of optimum blends of aqueous BZA and AEEA as a potential solvent for CO 2 capture. Therefore, the direct calorimetric measurements of the heats of absorption of CO 2 in aqueous (BZA + AEEA) is an important parameter to determine the design accuracy and the calculation of steam economy in the stripper section, which are not available till date in the open literature.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Kim and Svendsen have reported the experimental data on the heat of absorption of CO 2 in 30 wt % AEEA solution in a reaction calorimeter, which is the only available information in the literature on the direct calorimetric measurements of the enthalpy of absorption of CO 2 for the system (CO 2 + AEEA + H 2 O). The results on CO 2 solubility and physical properties in our previous study concluded the use of optimum blends of aqueous BZA and AEEA as a potential solvent for CO 2 capture. Therefore, the direct calorimetric measurements of the heats of absorption of CO 2 in aqueous (BZA + AEEA) is an important parameter to determine the design accuracy and the calculation of steam economy in the stripper section, which are not available till date in the open literature.…”
Section: Introductionmentioning
confidence: 77%
“…The CO 2 loading (α CO 2 ) in aqueous (2.71 mol BZA + 1.39 mol AEEA)·kg –1 water solution increased by 0.2 mol CO 2 ·mol –1 amine than that in the aqueous BZA solvent, which was also better than the performance (by 0.05 mol CO 2 ·mol –1 amine) shown in the aqueous (2.03 mol BZA + 2.09 mol AEEA)·kg –1 water solution. Therefore, considering the physical properties of AEEA (higher viscosity and density than in aqueous BZA), the aqueous (2.71 mol BZA + 1.39 mol AEEA)·kg –1 water solution among all of the studied aqueous amine solutions might be used as an effective and economical solvent in postcombustion CO 2 capture applications with better CO 2 loading capacity and lower amine regeneration and pumping cost.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gao et al [ 20 ] identified that the mixture of MEA and BZA would form a precipitate with a high CO 2 load. Mukherjee et al [ 21 ] used an artificial neural network (ANN) model to predict the CO 2 solubility of a mixture of BZA and N-(2-aminoethyl)-ethanolamine (AEEA). Zheng et al [ 22 ] investigated the reaction kinetics of BZA with CO 2 using a stopped-flow apparatus.…”
Section: Introductionmentioning
confidence: 99%